(untitled) (Sains Humanika, 2022)
The advancement of the country’s development aligning with Industrial Revolution 4.0 has required talents that possess knowledge in the science and technology field. Besides, graduates should also equip themselves with a variety of soft skills and thinking skills to deal with challenges or make new opportunities. As such, students in the current generation have adapted to many learning approaches, which include online learning. Multiple approaches have been introduced in Malaysian curriculum to sharpen students’ thinking skills and diversify their learning opportunities, yet one of them is problem-based learning (PBL). However, there is scarce number of research contribute to the learning of chemistry through online lesson utilizing PBL approach. This research aimed to 1. Develop a problem-based learning teaching module for the topic of carbon compounds for physical and online classrooms and 2. Identify the suitability of the teaching module to be applied in the physical classroom and online lesson. This study utilized ADDIE instructional model in constructing the module. The module was constructed according to the chemistry national curriculum on the topic of carbon compounds. The validation of the module has a remarkable comment in terms of fulfilment of objectives, suitability of method of delivery the module content and the relevance of the problem used to sharpen student’s cognitive skills. The validators also added suggestions for improvement of the PBL module which is to explain how PBL works and provide more explanation on the problems.